2016
DOI: 10.1055/s-0036-1597088
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Effect of Intra-articular Platelet-Rich Plasma Injection on Union: Pain and Function Improvement in Patients with Scaphoid Fracture

Abstract: Introduction Fracture of the scaphoid bone is the most common fracture of the carpus. However, the fracture union occurs late or may not heal. Sometimes, fracture healing requires prolong immobilization. Because of potential for joint stiffness, muscle atrophy, or the inability to use the hand during and after prolonged immobilization, there is great incentive to develop therapies that will accelerate bone healing and allow a quick return to work. To date, the effect of platelet-rich plasma (PRP) on scaphoid f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 22 publications
(24 reference statements)
0
10
0
Order By: Relevance
“…Our study demonstrates that staple is useful in treating waist SNUs and that GPRP is useful to improve healing, which is in agreement with other studies on bone healing. 8 9 10 12 13…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study demonstrates that staple is useful in treating waist SNUs and that GPRP is useful to improve healing, which is in agreement with other studies on bone healing. 8 9 10 12 13…”
Section: Discussionmentioning
confidence: 99%
“… 10 There is no consensus on the benefit of PRP apposition in fracture healing. 11 Evidence on the use of PRP in SNU is still lacking, 12 although its application has been already investigated applied on a bone graft. 13 The aim of the study was to investigate the role of gelled PRP (GPRP) in patients with SNU (later than 6 months from fracture diagnosis or fracture occurrence) treated surgically with staple osteosynthesis, without bone autograft.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, based on the SUCRA results of this NMA, PRP was another effective regime, as it ranked the first in pain reduction (0.691) and the second in stiffness (0.603), physical function (0.608), and total scores (0.624). A RCT study found that compared with therapeutic exercise alone, PRP injections and therapeutic exercise combination treatment could be more effective in reducing pain and improving stiffness as well as quality of life [ 32 ]. Another prospective, double-blind RCT supported that PRP injections had a better short-term effectiveness than placebos in the reduction of pain and stiffness and the improvement of knee function in early knee OA [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Once the cells are cultured in the environment with PRP, the fibrin and a variety of growth factors released from platelets have synergistic effect on cells' behavior. Namazi and Kayedi [ 23 ] indicated PRP may have a significant therapeutic effect on pain relief at rest and alleviate function difficulties including specific and usual activities in patients with scaphoid fractures in a study with 14 patients enrolled. Ghaffarpasand et al [ 24 ] determined that application of PRP along with autologous bone graft in the site of nonunion of long bone after intramedullary nailing or ORIF resulted in high cure rate, short duration of healing, low rate of limb shortening, and mild postoperative pain.…”
Section: Discussionmentioning
confidence: 99%